Particle technology and engineering : an engineer's guide to particles, powders and multiphase systems /: an engineer's guide to particles, powders and multiphase systems. (2015) - Seville, Jonathan P. K; (Professor of chemical engineering), Wu, Chuan-Yu
No abstract available